Eine neue Artengruppe der Gattung Odeles Klausnitzer, 2004 sowie die Beschreibung einer neuen Art aus Myanmar (Birma) (Coleoptera, Scirtidae) - (116. Beitrag zur Kenntnis der Scirtidae). - Klausnitzer, Bernhard (Contributions to Entomology = Beiträge zur Entomologie, 2005)
A new species (Odeles marggii n. sp.) and species-group (Odeles marggii species-group) in the genus Odeles Klausnitzer, 2004 is described. Most significant character is the hornlike structure on the frontoclypeus of the male. Fine structure indicates the probable existence here of the opening to a glandular field.KeywordsScirtidae, Odeles, new species, new species-group, hornlike structure, glandular field, Myanmar, Birma.Nomenclatural Actsmarggii Klausnitzer, 2005 (Odeles), spec. n.